Dynamic simulation of a liquefied hydrogen export terminal - Restelli,F; Jiao,F; Norris,B; Trusler,JPM; Siahvashi,A; May,EF; Pellegrini,LA; Johns,M; Al,Ghafri SZS (Energy, 2026)
At prospective liquid hydrogen (LH2) export terminals, managing boil-off gas (BOG) presents a significant challenge that has not been adequately explored in the literature. This work is a case study examining the management of BOG evolved during storage and carrier loading at an export terminal, carried out using detailed dynamic simulations. The considered terminal operates with a LH2 production rate of 450 t/d, and a carrier capacity of 160000 m3. The normal operation cycle spans a period of 28 days, during which all the generated BOG is recovered. The estimated levelized cost for terminal storage and shipment is 2.77 USD/kg, underlining the need for further research to reduce costs and enhance the economic viability of LH2 export. A sensitivity analysis indicates that the production rate primarily affects the duration of the normal operation cycle and, consequently, shipping frequency, while feed pressure and ortho-para hydrogen composition significantly influence total BOG generation.